Development and validation of a physical activity games playability scale (PAGPS) - Eng Wah, T.; Weimo, Z. (2015)

(untitled)
Children’s interest and participation rates in daily physical education (PE) declines with age (CDC, 2008). In contrast, engagement time on sedentary activities e.g., watching television and computer gaming is on the rise (CDC, 2009; Hancox & Poulton, 2006). In line with goal to reduce childhood obesity and promotion of active lifestyle; the reintroduction of fun physical activity (PA) games could hold the key to achieving this goal. Caillois (1961) suggested that PA games could lead to better health, fun, enjoyment, relaxation and a chance to develop skills. Even though children’s PA games (e.g., playground games, street games, party games, or traditional games) have long been incorporated into PE classes and other recreational settings, little work has focused on how to select fun and interesting PA games.